Beta-blocker management in patients admitted for acute heart failure and reduced ejection fraction: a review and expert consensus opinion - Schurtz, Guillaume; Mewton, Nathan; Lemesle, Gilles; Delmas, Clément; Levy, Bruno; Puymirat, Etienne; Aissaoui, Nadia; Bauer, Fabrice; Gerbaud, Edouard; Henry, Patrick; Bonello, Laurent; Bochaton, Thomas; et al. (Frontiers in Cardiovascular Medicine, 2023)
The role of the beta-adrenergic signaling pathway in heart failure (HF) is pivotal. Early blockade of this pathway with beta-blocker (BB) therapy is recommended as the first-line medication for patients with HF and reduced ejection fraction (HFrEF). Conversely, in patients with severe acute HF (AHF), including those with resolved cardiogenic shock (CS), BB initiation can be hazardous. There are very few data on the management of BB in these situations. The present expert consensus aims to review all published data on the use of BB in patients with severe decompensated AHF, with or without hemodynamic compromise, and proposes an expert-recommended practical algorithm for the prescription and monitoring of BB therapy in critical settings.